ESP for Medical Students in Yemen : A Study Investigating the Match and Mismatch of Student and Faculty Perceptions - Wafa, Ahmed Farea; Majed Ahmed, Al-Mansoub; Manjet Kaur, Mehar Singh (Secholian Publication, 2024)
This study aims to gather information about the lacks and wants of existing ESP for medical students at Ibb University (IU) in Yemen as a part of a needs analysis with descriptive quantitative and qualitative methods. In this study, the quantitative data were collected using questionnaires (n=200) via the maximum variation purposive sampling strategy, while the qualitative data were obtained from semistructured interviews (n=29) via convenience sampling. The statistical analysis was conducted using IBM® SPSS® Statistics V24. Descriptive statistics analysis involving means and frequencies was used to analyse the quantitative data. In addition, thematic analysis was used to analyse the qualitative data collected from semi-structured interviews. The inferential statistical procedures, using a nonparametric Kruskal-Wallis (K-W) and Mann-Whitney U, were applied to determine any significant differences regarding the English language lacks and wants of the current ESP course. The findings revealed that medical students were proficient in using main English language skills (i.e., reading and listening) but had major weaknesses in grammar, pronunciation and communication skills. Besides, English sub-skills such as reading textbooks, reading course handouts, reading study notes, writing test/exam answers, following lectures, following question/answer sessions in class, and participating in discussions were used proficiently by medical students as perceived by the three groups of respondents. Medical students are required to have more training in speaking and writing. Based on these findings, the present study concluded that conducting a needs analysis is crucial in designing effective ESP courses. Finally, some pedagogical implications would help tap for course designers and recommendations for future studies.